Análisis de las normas internacionales de información financiera niif´s aplicadas en el año 2012 en el centro de dialisis Cornelio Samaniego Cia. Ltda. - Cacay Soto, Edison Leonel (2016)
This thesis Entitled "ANALYSIS OF INTERNATIONAL FINANCIAL REPORTING IFRS APPLIED IN 2012 IN THE CENTRO DE DIÁLISIS CORNELIO SAMANIEGO CIA. LTDA. ” have performed in order to fulfill a prerequisite to choose the Engineering degree in Accounting and Auditing, development comes under the International Financial Reporting for Small &medium entities, International Accounting Standards, and other laws force in our country (Ecuador) for their operation to be made available to the manager. Its formal structure is an input of the work highlighting the importance of the subject investigated. In the literature review develops the theoretical foundation containing from the kinds of company that owns our company to investigate a summary of each of the sections of IFRS according to my criteria I should have be studied. This followed by the execution of the analysis being based on a tripod: Diagnosis of the financial statements of December 31, 2011 and its transformation to January 2012 and also those of December 31, 2013, to serve as a basis to examine whether the company has its financial statements in accordance as provided by the control entity SIC(Superintendencia de Compañias) , Analysis This phase analyzes the accounts of peak within the financial statements as you contrast between the accounting policies of the company and the Rules Hospitalizations issued by the IASB; Report issued the findings and recommendations to the manager about the analysis of International Standards adopted. Based on the results obtained it was drawing conclusions on the most relevant aspects of the work, and then formulate the respective recommendations aimed at improving the shortcomings found in the company, which is why we can mention that it has met all targets established at the beginning of the project.